DEVELOPMENT OF CLUSTERS IN THE METALLURGICAL INDUSTRY: FEATURES AND PROSPECTS (Лучшие интеллектуальные исследования, 2025)
Annotation: The article examines the key aspects of the development of cluster structures in the metallurgical industry of the Republic of Uzbekistan, analyzes their features and potential benefits for the country's economy.